The Controversy Surrounding the Intercountry Adoption - Murányi, Fanni (METSZETEK Társadalomtudományi Folyóirat, 2015)
The purpose of this article is to identify characteristics of the legal framework of intercountryadoption. This study is specifically concerned with the international and Hungarian legislation.In the first part, the international conventions and the Hungarian rules are presented. Theseshow that a considerable progress has been made in the last century in law-making.A short statistical analysis illustrates the role of Hungary in intercountry adoption.The final section considers possible risks and abuses in the process: exploitation, familytracing, loss of cultural heritage, over-representation Roma children, debate over closed oropen adoption and adoption agencies.On the basis of the results of this study, it can be concluded that the intercountry adoptiongives rise to a great debate and serious cause for complaining about abuses which weaken thechildren’s rights.This dissertation hopes to offer a comprehensive view on the advantages and challenges ofintercountry adoption.